GRANTING MYCORRHIZAL AND SLUDGE TO INCREASE PRODUCTION PLANT OF PEANUT (Arachis hypogaea L) - Farida Hariani; Erlita , (AGRIUM: Jurnal Ilmu Pertanian, 2016)
Giving mycorrhiza can improve nutrient uptake P plant, while Sludge can fertilize the soil. The use of organic fertilizer such as sludge has many benefits when applied in fertilizing agricultural crop land. The emphasis on the use of organic fertilizers continuously and sustainably will provide advantages and benefits in the long-term use. This study aimed to evaluate the response of groundnut crop production due to the provision of mycorrhizal and sludge as well as their interactions.The research was conducted at the experimental station road.Bunga Ncole  XXII. Victory Urban Village Farmers. Tuntungan district of Medan, North Sumatra Province in April to August 2015. The material used is peanut seeds varieties bison, mycorrhizal, sludge.The design used was a randomized block design factorial with two treatment factors. The first factor sludge (S), which consists of 4 levels, namely: S0 = 0 g / plant (without giving sludge); S1 = 90 g / plant; S2 = 180 g / plant and S3 = 270 g / plant. Factors to two mycorrhizal administration consists of three levels ie: M0 = 0 g / plant (without giving mycorrhizae); M1 = 10g / plants; M2 = 20 g / plant.                The parameters measured were Number of pods per plant (pod), weight of 100 grains dry beans (g) and uptake of plant nutrients P (%). The results obtained for the provision of mycorrhizae show a marked influence on the weight of 100 grains dry beans with the highest production are on M2 (70.50 g) while the parameter Number of pods per plant and plant nutrient uptake P showed no significant effect. Giving sludge showed significantly different influence on the parameters of the dry weight of 100 grains dry beans where production is highest in the S2 (68.22 g). while for the parameter Number of pods per plant and plant nutrient uptake P showed no significant effect. Interactions between giving mycorrhizal  and sludge shows the real effect on nutrient absorption parameter P S1M2 plants where the combination treatment (0.32%) showed the highest plant nutrient uptake P, while the parameter Number of pods per plant and weight of 100 grains 100 dry seeds showed different influences not real .Keywords: Mycorrhizae, Sludge, Peanut, growth.